Sosialisasi Sadar Wisata sebagai Upaya Peningkatan Partisipasi Aktif Masyarakat Guna Mewujudkan Pariwisata Budaya Berkelanjutan di Desa Wisata Tanon Kabupaten Semarang - Paranti, Lesa; Farkhatunnisa, Alif; Fauzizah, Ardha Dwi; Wafa, Mochammad Usman; Zulfa, Nely (Universitas Negeri Semarang, 2023)
Dusun Tanon is one of the hamlets in Ngrawan Village, Getasan District, which was officially established as a tourism village on April 21, 2012. This socialization aims to increase tourism awareness for the people of Tanon Hamlet by organizing tourism awareness socialization activities towards sustainable tourism. The implementation method used in Community Service uses counseling methods through material presentation and discussion approaches. Also, the evaluation method uses price as the level of satisfaction in supervising socialization activities. With this outreach, participants understood the material presented regarding community awareness and tourism promotion, and took an active part in the discussion sessions. Through this tourism awareness socialization activity, it is hoped that it can increase the active participation of the community in strengthening tourism villages towards sustainable cultural tourism.